2018
DOI: 10.1186/s13045-017-0547-3
|View full text |Cite
|
Sign up to set email alerts
|

The polycomb group protein EZH2 induces epithelial–mesenchymal transition and pluripotent phenotype of gastric cancer cells by binding to PTEN promoter

Abstract: BackgroundThe influences of oncogenic Ezh2 on the progression and prognosis of gastric cancer (GC) and the underlying mechanisms are still poorly understood. Here, we aimed at investigating clinicopathological significance of Ezh2 in GC and the mechanisms underlying its function in GC development.MethodsThe expression level of Ezh2 was determined by qRT-PCR, immunoblot, and immunohistochemistry analysis in 156 pairs of GC tissues and adjacent normal gastric mucosa tissues. The biological functions of Ezh2 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 39 publications
8
83
0
Order By: Relevance
“…UFC1 repressed PTEN expression via the recruitment of EZH2 and the subsequent epigenetic modification. Our results are consistent with those reported by Gan et al showing that EZH2 induces EMT and pluripotency of gastric cancer cells by suppressing PTEN expression 34 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…UFC1 repressed PTEN expression via the recruitment of EZH2 and the subsequent epigenetic modification. Our results are consistent with those reported by Gan et al showing that EZH2 induces EMT and pluripotency of gastric cancer cells by suppressing PTEN expression 34 .…”
Section: Discussionsupporting
confidence: 94%
“…The recent studies have shown that EZH2 regulates diverse cellular processes and participates in cancer development, progression and metastasis. Many lncRNAs bind to EZH2 to epigenetically silence gene expression in NSCLC cells [22][23][24][25][26][27][28][29][30][31][32][33][34] , such as TUG1 22 , ANRIL 23 , PANDAR 24 , PVT1 25 , and PCAT6 26 . These lncRNAs interact with EZH2 and regulate the expression of distinct target genes, including p21, KLF2, p57, Bcl2, LATS2, and p57.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that overexpression of the regulator of G-protein signaling pathway 1 (RGS1) might promote the transition of stem cells into CSCs [308]. Besides, CSCs are involved in EMT progression via a vast number of mechanisms, including an overactivation of KRAS, STAT3, Rac1, Wnt, Notch, PTEN, ERK, NF-κB signaling pathways, or hypoxic microenvironment [309][310][311][312][313][314][315][316][317][318]. Recently, researchers have proposed the role of CSC-associated protein, leucine-rich repeat and immunoglobulin-like domain-containing nogo receptor-interacting protein 2 (LINGO2), in gastric cancer and EMT initiation [319].…”
Section: Stem Cellsmentioning
confidence: 99%
“…15,16 Moreover, PTEN could be suppressed by EZH2 through the enrichment of H3K27me3 on its promoter region in various cancers. 17,18 Thus, we wondered whether PCAT-1 epigenetically repressed PTEN through EZH2 in GC. First, starBase analysis demonstrated that PCAT-1 was positively correlated with EZH2 level in STAD tissues (n = 375) from TCGA ( Figure 3A).…”
Section: Pcat-1 Epigenetically Silenced Pten In Bgc823/cddp Cellsmentioning
confidence: 99%